Clinical Significance of Increasing Pressure Curve's Slope When Injecting Ultrasound Contrast Agent During Evaluation of Fallopian Tubal Patency. (9th January 2021) - Qiang, Ye; Wu, Yiyun; Cai, Ting
Abstract : Objective: To explore the association between Fallopian tubal patency and the slope of the increasing pressure curve for ultrasound contrast agent. Materials and Methods: A total of 136 patients underwent transvaginal 4‐dimensional hysterosalpingo‐contrast sonography (TVS 4D HyCoSy) between August 2015 and January 2016. We divided the patients into 3 groups according to different Fallopian tubal patency status: 71 patients (48.97%) in bilateral tubal patency group, 45 (31.03%) in unilateral tubal patency group, and 20 in bilateral tubal nonpatent group. The ultrasound contrast agent was injected and the pressure curve was recorded automatically in real time using a liquid‐injecting machine that traces it as a pressure curve. The slopes of the different groups are compared through independent sample t test. Results: The slopes of the 3 groups were 1.242 ± 0.572, 1.472 ± 0.638, and 2.068 ± 1.236 kPa/s. A correlation was observed between the slope of the increasing pressure curve and tubal patency (R = 0.287, P < .05). The slopes differed significantly between the bilateral tubal patency group and bilateral tubal nonpatent group (P = .001) and between the unilateral tubal patency group and bilateral tubal nonpatent group (P = .012). However, the difference between the bilateral tubal patency and unilateral tubal patency groups was not significant (P = .266). Conclusion: The increase of the injecting pressure curve's slope for contrast agent during 4D HyCoSy is associated with the nonpatent degree of the tube. This condition can be used as an objective index of tubal patency and can be a reference in diagnosis and treatment.